2014
DOI: 10.1139/apnm-2013-0133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on brain-derived neurotrophic factor levels and oxidative damage in obesity and diabetes

Abstract: We evaluated the effects of curcumin treatment on protein oxidation (PO), lipid peroxidation (LP) and brain-derived neurotrophic factor (BDNF) levels in the hippocampus and frontal cortex (FC) of diabetic db/db mice (DM) and in sera of obese humans. Thus, DM were treated daily with 50 mg/kg of curcumin during an 8-week period. Obese human were treated daily with 500 and 750 mg of curcumin that was administered orally for 12 weeks; BDNF, PO and LP levels in sera were determined at in weeks 0, 2, 6 and 12 of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 49 publications
3
44
0
2
Order By: Relevance
“…The progressive loss of renal function could make it necessary for the patient to receive renal replacement therapy such as hemodialysis, and the progressive loss of circulating levels of BDNF should be prevented in patients with DM2 to avoid premature cognitive decline. There have been several experimental studies with curcumin[40] and resveratrol, both of which increase serum BDNF levels. Curcumin has an antidepressant effect, mediated by its antioxidant activity and up-regulation of phosphor Akt and mTOR levels in the hippocampus and prefrontal cortex[41].…”
Section: Discussionmentioning
confidence: 99%
“…The progressive loss of renal function could make it necessary for the patient to receive renal replacement therapy such as hemodialysis, and the progressive loss of circulating levels of BDNF should be prevented in patients with DM2 to avoid premature cognitive decline. There have been several experimental studies with curcumin[40] and resveratrol, both of which increase serum BDNF levels. Curcumin has an antidepressant effect, mediated by its antioxidant activity and up-regulation of phosphor Akt and mTOR levels in the hippocampus and prefrontal cortex[41].…”
Section: Discussionmentioning
confidence: 99%
“…In total homogenate of placenta tissue, lipid peroxidation levels were quantified with the thiobarbituric acid-reactive substances (TBARS) assay as we previously described [16, 17]. …”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that higher concentration of Cur can induce neuronal apoptosis and act as an anti-cancer agent [46][47][48]. Although the mechanistic details of how Cur restored HSPs after Aβ42 exposure, or how they induce HSPs in SH-SY5Y cells, is still unclear to us, one possible explanation may be that Cur treatments confer neuroprotection by secreting several growth factors, including BDNF, NGF and IGF [49][50][51]. Although we did not investigate these neurotropic factors in the present study, we found Cur restores BDNF in other animal models of neurodegenerative diseases.…”
Section: Although the Mechanistic Details Of Neuroprotection By Cur Imentioning
confidence: 99%